Benarkah Fat Talk Memicu Body Dissatisfaction pada Remaja Putri Pengguna Instagram? - Nur Kholifah; Khairunnisa Syarif (LPPM Universitas Abdurrab, 2025)
Teenage girls who use Instagram are currently exposed to unrealistic beauty standards, where filters, influencers, and ideal appearance content flood their feeds every day. This phenomenon not only shapes how teenagers view their own bodies, but also triggers negative body talk, which may increase the risk of body dissatisfaction among them. Therefore, this study aims to examine the relationship between fat talk and body dissatisfaction among teenage girls who use Instagram in Pekanbaru. This study involved 216 respondents aged 10–22 years. This study used validated and reliable scales for fat talk and body dissatisfaction. The results of the analysis showed a positive and significant correlation between fat talk and body dissatisfaction (r = 0.726, p <0.05), indicating that frequent engagement in fat talk can increase the tendency toward body dissatisfaction.